Peranan Penyusunan Laporan Keuangan Dalam Penyajian Informasi Keuangan Pada BMT At-Taqwa Muhammadiyah Sumatera Barat - Leli Wita Suwita (Universitas Negeri Padang, 2020)
This study aims to analyze how the role of financial statement preparation is to find out information relating to the financial position and performance of a corporate entity which includes the realization of the budget report, balance sheet, cash flow statement, and reports on the financial statement notes. The research method used is a qualitative method that compares financial statements between 2016 and 2018. The financial statements presented by BMT At-Taqwa Muhammadiyah West Sumatra in the form of a balance sheet and income statement, where an increase in value from the reporting date of the current year with the previous year, of the report there are still shortcomings in the reporting. BMT At-Taqwa Muhammadiyah West Sumatra is recommended to make all financial reports needed by financial information from BMT At-Taqwa Muhhammadiyah West Sumatra.Keywords: Role; Financial Statements; Financial Information.